The EU's Private Law in the Regulated Sectors: Competitive Market Handmaiden or Institutional Platform?. Issue 5 (September 2016) - Svetiev, Yane
Abstract: The article contests the claim that EU private law is narrowly circumscribed by a market rationality. Such a claim tracks broader criticism of EU functional legal integration, although it tends to obscure the underlying transformative pressures on private law and regulation and the role EU law plays in coping with such pressures. To offer a number of counter‐narratives, the article draws on examples from the regulated sectors, including telecommunications and energy, to reveal their experimentalist features. These suggest that EU private law is constructed through a process of error‐corrections, which allows for mutual adjustment of instruments and hybridisation of EU and local policy goals. The process results in more finely grained assemblages of autonomy and regulation to respond to concrete problems or newly salient policy goals, so that markets are understood as social institutions that are always works‐in‐progress rather than convergence points. Thus, EU private law provides a platform for transnational market‐building through innovating institutions that promote various normative and policy commitments despite the interdependencies that could undermine them.